The meaning of parental and peer support for elementary school children’s physical activity - Sahbana Ridha; Eko Wahyudi (Lambung Mangkurat University, 2026)
Background: Physical activity participation among Indonesian elementary school children remains concerningly low, with 58% failing to meet daily recommendations. Objectives: This study explores the meaning of parental and peer support for children’s physical activity participation within Indonesian families whose children engage in futsal extracurricular activities at an Islamic school in Banjarbaru. Methods: This qualitative phenomenological study involved 20 parents of children enrolled in futsal activities. Data were collected through in-depth interviews, focus group discussions, and observations using purposive sampling. Thematic analysis followed Braun and Clarke’s framework. Results: Seven interconnected themes emerged. Parents demonstrated behavioral modeling through active lifestyles, provided emotional support via encouragement and praise, and offered instrumental support, including equipment, transportation, and a monthly financial investment (Rp300,000-Rp1,000,000). Peer support strengthened participation through shared identity and healthy competition. Socioeconomic variations influenced support forms, yet emotional commitment remained consistent. Gender dynamics showed progressive attitudes toward girls’ participation. Families employed adaptive strategies to overcome barriers. Conclusion: Parental and peer support synergistically sustain children’s physical activity participation. Multi-level interventions strengthening family and peer systems while respecting cultural values are essential for promoting inclusive physical activity among Indonesian elementary school children.